Analysis of Speed Related Behavior of Kuwaiti Drivers Using the Driver Behavior Questionnaire - Matawaha, Jamal Al; Jadaan, Khair; Freeman, Brian (Periodica Polytechnica Transportation Engineering, 2020)
The Manchester Driver Behaviour Questionnaire (DBQ) is widely used to measure driving styles and investigate the relationship between driving behaviour and accidents involvement. Recent evaluations of different population groups have taken place throughout the world, including countries in the Arabian Gulf. This study seeks to extend the application of the DBQ to Kuwait with its mix of native and expatriate drivers, by examining the relationships between speed-related behavior and accident involvement using a speed-related score (SRS). For this purpose, 536 respondents (425 Kuwaitis and 111 Non-Kuwaitis) were asked to complete a questionnaire based on the DBQ parameters as well as background information. The results showed that young Kuwaiti male drivers scored highest in most of the areas. Factor analysis resulted in four significant dimensions; speed-related violations, anger related violations, errors, and lapses. The study focused on the speed related violation score (SRS) as the dependent variable. The statistical analysis using ANOVA and t- test showed that there is a significant effect of such factors as accident involvement, age, gender, nationality, education level, driving experience and marital status. Some countermeasures to reduce accidents were identified focusing on those groups with higher SRS values.